(untitled) (Bangladesh Journal of Dental Research & Education, 2013)
In this 21st century pharmaceutical science has been focused on the delivery of drugs through the oral mucosa. The buccal mucosa has been investigated for mucoadhesive local drug therapy and the systemic delivery of therapeutic peptides and other drugs that are subjected to first-pass metabolism or are unstable within the rest of the gastrointestinal tract. This review focuses on the permeability features of oral mucosa and new potential mucoadhesive local delivery systems to treat oral diseases. DOI: http://dx.doi.org/10.3329/bjdre.v3i2.16612 Bangladesh Journal of Dental Research & Education Vol.3(2) 2013: 41-44